Analysis of Elementary School Teachers' Importance Level and Educational Needs for Improving the Career Education Competencies of Students With Disabilities - Park, Mi Hwa (Korean Journal of Physical, Multiple and Health Disabilities, 2022)
Purpose: The purposes of this study were 1) to examine elementary school teachers' perceptions of the importance of the career education competency of students with disabilities in elementary school, 2) to assess their level of implementation, and 3) to clarify the educational needs for improving career education. Method: A survey was conducted with elementary teachers in Gyeonggi-do. A total of 155 responses were collected and statistically analyzed using SPSS Statistics 26. Results: First, the elementary school teachers recognized the importance of the career education competency of students with disabilities more than the level of performance. Second, the implementation of the career education was the most significant factor for educational needs. The factor includes the implementation of creative, local, career-related field studies and activity programs as well as career counseling for the parents of students with disabilities. Third, the priority of educational needs depended on the teacher's class, the experience of inclusive education, and teaching experience. Conclusion: To educate and support prioritized competencies based on educational needs, a variety of practical training programs should be developed.
Keywords: career education competency; educational needs; students with disabilities